Level and areas of occupational aspiration of street children in Iloilo City Proper as affected by their ordinal position, size of family and educational level - Barrios, John E. (1994.)
This is a study on the effect of ordinal position, size of family and educational level on the level and areas of occupational aspiration of street children in Iloilo City proper. The study hypothesizes that there is no significant relationship in the level and areas of occupational aspiration of street children of vaired ordinal position, size of family and educational level. Chi-Square test for independence was used to find out if there is a significant relationship between the variables at 0.05 level of significance. The results show that street children in Iloilo City proper aspire for high level occupations falling into areas under Science, Technology and Culture-related; most of them are middle children, enrolled in the primary level and come from big families. The study suggests future researchers on the level and areas of occupational aspiration of street children should take into consideration the street children's performacne in school and the programs conducted by agencies concerned, especially those with their education and family therapy
Thesis (Undergraduate, Bachelor of Arts in Psychology-History) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Street children -- Iloilo City